2017
DOI: 10.1038/srep41494
|View full text |Cite
|
Sign up to set email alerts
|

Modeling pre-metastatic lymphvascular niche in the mouse ear sponge assay

Abstract: Lymphangiogenesis, the formation of new lymphatic vessels, occurs in primary tumors and in draining lymph nodes leading to pre-metastatic niche formation. Reliable in vivo models are becoming instrumental for investigating alterations occurring in lymph nodes before tumor cell arrival. In this study, we demonstrate that B16F10 melanoma cell encapsulation in a biomaterial, and implantation in the mouse ear, prevents their rapid lymphatic spread observed when cells are directly injected in the ear. Vascular remo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 47 publications
0
18
0
Order By: Relevance
“…For instance, mice overexpressing vascular endothelial growth factor (VEGF)-A or VEGF-C in a model of chemically induced skin carcinogenesis showed prominently enhanced LN lymphangiogenesis, concomitant with a significant increase of LN and distant organ metastasis ( Hirakawa et al., 2005 , Hirakawa et al., 2007 ). Importantly, these and other studies using experimental models of nasopharyngeal carcinoma ( Qian et al., 2006 ) and malignant melanoma ( García-Caballero et al., 2017 , Harrell et al., 2007 ) have identified the onset of LN lymphatic remodeling prior to the colonization of the LN by metastatic cells. These data suggest that, even in the absence of metastatic tumor cells, tumor-associated lymphangiogenic factors can be drained from the primary tumor or released by locally activated cells to initiate changes in preparation of a pre-metastatic “lymphovascular niche” ( Hirakawa et al., 2005 , Ogawa et al., 2014 , Olmeda et al., 2017 ).…”
Section: Introductionmentioning
confidence: 82%
“…For instance, mice overexpressing vascular endothelial growth factor (VEGF)-A or VEGF-C in a model of chemically induced skin carcinogenesis showed prominently enhanced LN lymphangiogenesis, concomitant with a significant increase of LN and distant organ metastasis ( Hirakawa et al., 2005 , Hirakawa et al., 2007 ). Importantly, these and other studies using experimental models of nasopharyngeal carcinoma ( Qian et al., 2006 ) and malignant melanoma ( García-Caballero et al., 2017 , Harrell et al., 2007 ) have identified the onset of LN lymphatic remodeling prior to the colonization of the LN by metastatic cells. These data suggest that, even in the absence of metastatic tumor cells, tumor-associated lymphangiogenic factors can be drained from the primary tumor or released by locally activated cells to initiate changes in preparation of a pre-metastatic “lymphovascular niche” ( Hirakawa et al., 2005 , Ogawa et al., 2014 , Olmeda et al., 2017 ).…”
Section: Introductionmentioning
confidence: 82%
“…In this model, sprouting lymphangiogenesis is reproduced in a complex in vivo microenvironment. This application is based on the use of a biomaterial, gelatin sponge that is inserted in the mouse ear to develop a large lymphatic network [ 145 ]. The gelatin sponge is cut into pieces of about 3 mm 3 , which are transferred in a 96-well plate (one sponge piece per well) for pre-treatment ( Fig.…”
Section: In Vivo Sprouting Lymphangiogenic Assay and Aav-mediated Gmentioning
confidence: 99%
“…The immunoregulatory components and their functions within niches have been thoroughly studied and recently reviewed ( 100 , 142 ). Several studies have progressively revealed the spatial distribution of immune and host stromal components within niches ( 143 – 145 ).…”
Section: Spatial Architecture Of the Time And Tumor Biologymentioning
confidence: 99%